The Readiness of Secondary Schools Teachers in Al-Nasiriyah City to Screening for Heart Disease: The Mediating Role of the Hypertension Beliefs and Behavior, Health Beliefs, and Heart-Healthy Behaviors - Hasan Hanoon, Zahraa; Kareem Farj, Raad (International Journal of Psychosocial Rehabilitation, 2020)
Objectives: The study aims to determine teachers’ readiness to screen for heart disease. To find out the association between teachers’ age, gender, marital status, BMI, education qualification, years in education, hypertension beliefs and behaviors, heart health behaviors, and their readiness to screen for heart disease. Methodology: A descriptive study is carried out on teachers of secondary schools in Al-Nasiriyah City. A convenience (non-probability) sample of 344 teachers of secondary schools. The data collection has been initiated from January 26th, 2020, to March 14th, 2020. The research instrument consists of three parts: the first part contains demographic data, the second part focuses on participants’ heart behaviors questionnaire, and the third part is related to hypertension belief and behavior. Descriptive and inferential statistical data analysis approaches have been used. Results: The result of the study revealed that less than a half of teachers age at 22-30 years (n = 155), participants are equally distributed between males and females (n = 172), more than a half are married (59.9%), and the majority hold a bachelor’s degree (81.1%), as shown in Table 1. Around a half of the participants are within normal weight (49.7%). More than two-fifths do not know their systolic and diastolic blood pressure. Most of the teachers do not know their cholesterol level (n = 253), and the majority do not know their HDL level (85.5%). More than a half reported that they do not have such family history (56.7%). Conclusion: The study conclusion has included more than half who are not ready to perform heart disease testing. Recommendations: The study has recommended that follow-up check blood pressure periodically and follow-up on continuous checks for cholesterol and HDL. Follow up on continuous checks for cholesterol and HDL Follow preventive measures to prevent hypertension.